2015
DOI: 10.1155/2015/973154
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bisphenol A Level in Boys with Cryptorchidism: A Step to Male Infertility?

Abstract: Cryptorchidism is the most common congenital birth defect in boys and affects about 2–4% full-term male neonates. Its etiology is multifactorial. Purpose. To evaluate the serum bisphenol A (BPA) levels in boys with cryptorchidism and healthy boys and to assess the risk of environmental exposure to BPA using the authors' questionnaire. The data were acquired from a study on boys with cryptorchidism (n = 98) and a control group (n = 57). Prior to surgery, all patients had BPA serum levels evaluated. The size, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…)21Fenichel et al . (2012)Southern FranceFrench studies on cryptorchidism in Nice and GrasseCase-referent46/106CryptochidismCord bloodBisphenol AMean unconjugated Bisphenol A marginally higher in cases but not significant ( P = 0.38)61Komarowska et al . (2015)PolandChildren 0–4 years admitted to paediatric departmentCase-referent98/57CryptochidismSerumBisphenol AFree serum BPA level in cryptorchid boys and in the control group was not statistically significant but the conjugated and total serumBPA level was elevated in cryptorchid boys31

a CR: completeness of reporting on a scale from 0 (low completeness) to 11 (high completeness).

b Bias and confounding: 1 = higher risk of bias, 0 = lower risk of bias.

…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…)21Fenichel et al . (2012)Southern FranceFrench studies on cryptorchidism in Nice and GrasseCase-referent46/106CryptochidismCord bloodBisphenol AMean unconjugated Bisphenol A marginally higher in cases but not significant ( P = 0.38)61Komarowska et al . (2015)PolandChildren 0–4 years admitted to paediatric departmentCase-referent98/57CryptochidismSerumBisphenol AFree serum BPA level in cryptorchid boys and in the control group was not statistically significant but the conjugated and total serumBPA level was elevated in cryptorchid boys31

a CR: completeness of reporting on a scale from 0 (low completeness) to 11 (high completeness).

b Bias and confounding: 1 = higher risk of bias, 0 = lower risk of bias.

…”
Section: Methodsmentioning
confidence: 98%
“…Studies reporting alternative measures of association such as difference in mean values of exposure levels in cases and controls were also included, and the authors were contacted to get risk estimates (Hosie et al ., 2000; Damgaard et al ., 2006; Main et al ., 2007; Choi et al ., 2012; Fenichel et al ., 2012; Komarowska et al ., 2015; Virtanen et al ., 2012). Several authors responded positively but reanalysis of the original data could not be accomplished within the given time-frame and the studies were therefore not included in the present review.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have observed higher levels of the compounds bisphenol A , 176 dibutylin 169 dioxin , 164,173 heptachloroepoxide , 174 hexachlorobenzene , 174 polychlorinated biphenyls 164,173,177 and polybrominateddiphenyl ethers 159,164 among boys (and/or their mothers) who developed cryptorchidism compared to those who did not; however a substantial number of studies (at least some of which were adequately powered to detect an association) have directly evaluated these and other biologically-plausible compounds and found no such association. 56,60,152157,160,163,168,172,178 In some cases, studies have found substantial regional heterogeneity, including conflicting results between countries within the same study.…”
Section: Endocrine-disrupting Chemicalsmentioning
confidence: 99%
“…Those studies investigating early-life environmental exposure to endocrine-disrupting chemicals as a risk factor for cryptorchidism have generally drawn blood from the children themselves. 175,176 …”
Section: Endocrine-disrupting Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation